Introduction to econometrics - Dougherty, Christopher (Oxford University Press, 2002)
Introduction to Econometrics,2/e offers a step-by-step introductory guide to the core areas of econometrics. Accessible to readers with limited mathematical backgrounds, the book provides an analytical and an intuitive understanding of the classical linear regression model. This new edition has been substantially updated and revised with the inclusion of new material on specification tests, binary choice models, tobit analysis, sample selection bias, nonstationary time series, and unit root tests and cointegration